Domestic animal behaviour and welfare - Fraser, Andrew F. (CABI, 2007)
"Behaviour is a significant indicator of health in animals and understanding behaviour is the key to good management. Animal behaviour and animal welfare science are fast becoming core topics in the curricula of agriculture and veterinary students." "The eagerly awaited fourth edition of Farm Animal Behaviour and Welfare has a new title to reflect its expansion to include companion animals. Domestic Animal Behaviour and Welfare builds on the coverage of the previous edition, fully updating it to take into account developments over the last 10 years. It is an indispensable textbook for students and practitioners, covering major and growing areas in agricultural and veterinary science and practice."--Jacket